2018
DOI: 10.3390/urbansci2010014
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity of Sustainable Transportation Offer Values: A Comparative Analysis of Nantes Urban and Periurban/Rural Areas (France)

Abstract: Abstract:Innovative solutions have been implemented to promote sustainable mobility in urban areas. In the Nantes area (northwestern part of France), alternatives to single-occupant car use have increased in the past few years. In the urban area, there is an efficient public transport supply, including tramways and a "busway" (Bus Rapid Transit), as well as bike-sharing services. In periurban and rural areas, there are carpool areas, regional buses and the new "tram-train" lines. In this article, we focus on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…The fluctuations in the perceived values of environmental variables across space are consistent with the literature. Bulteau et al 2018 found a similar result in their study of the impacts of sustainable transportation on housing markets in France. In some regions there was a surprising disutility associated with transportation, despite the general positive relationship, and the authors surmised that it might relate to noise pollution and other negative externalities of transportation systems [36].…”
Section: The Value Of Environmental Amenities In Greenville Countysupporting
confidence: 64%
See 1 more Smart Citation
“…The fluctuations in the perceived values of environmental variables across space are consistent with the literature. Bulteau et al 2018 found a similar result in their study of the impacts of sustainable transportation on housing markets in France. In some regions there was a surprising disutility associated with transportation, despite the general positive relationship, and the authors surmised that it might relate to noise pollution and other negative externalities of transportation systems [36].…”
Section: The Value Of Environmental Amenities In Greenville Countysupporting
confidence: 64%
“…In the hedonic modeling literature, GWR has been shown to improve global estimates by accounting for local spatial variation [33,34]. Hedonic models employing GWR have found spatially contingent relationships between housing values and proximity to transportation systems [35,36], and between air quality and housing prices in the USA [37]. A study in Austria used spatial regression to demonstrate that locally weighted models are the most appropriate for informing local planning and policy [38].…”
Section: Introductionmentioning
confidence: 99%
“…Hedonic analyses have been conducted at different spatial scales, mainly representing administrative units, i.e., a county [17] or municipality [18] and its districts [19], sub-national [20], and country [21]. The peri-urban context [22] has not yet been well described in the hedonic pricing literature. Therefore, our research extends the existing body of valuation literature of environmental amenities with a peri-urban hedonic pricing case study and discusses its practical implications for authorities being responsible for the peri-urban environment.…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods in spatial econometrics (Bulteau, Feuillet and Le Boennec 2018;Latinopoulos 2018) (Fotheringham, Brunsdon and Charlton 2002). We decided to use the first category of model for the following reasons: (i) The spatial Durbin model cannot be used here as one of the main purposes of the analysis is to capture the effects of public and network attributes.…”
Section: Model Specificationmentioning
confidence: 99%